Quantificação da gravidade do enfisema pulmonar a partir de imagens de tomografia computadorizada de tórax - Ferreira, Rhenan Bartels (2019)
The present study aimed to propose a method to quantify the loss of lung tissue mass (LTM) in regions of low X-ray attenuation and to evaluate the increase of LTM in regions of high attenuation using the quantitative analysis of computed tomography (CT) images of patients with emphysema from different etiologies. Thus, 16 subjects with alpha-1 antitrypsin deficiency emphysema (A1ATD), 21 with emphysema due to smoking (Non-A1ATD) and 27 healthy individuals with no smoking history (Control) were studied. The volunteers underwent pulmonary function tests (PFT) and underwent CT imaging during inspiration and expiration. The LTM content associated with 3, 15 and 50% (M3, M15 and M50) fractions of total lung capacity (TLC) and the complement of the LTM associated with 3, 15 and 50% (M97c, M85c and M50c) of the denser regions were calculated and compared among the groups. The parameters for fitting the monoexponential curve of lung volume versus LTM were used to compare the groups and to correct the effect of lung volume on the indices calculated in this study. Patients with emphysema exhibited reduced LTM compared to the Control group when compared with M3, M15 and M50 indices and presented higher LTM in high density regions reflected by the indices M97c, M85c and M50c. In addition, there was a statistically significant association (p<0.001 and r ≥ 0.70) between M15 and the PFT variables. In conclusion, the evaluation of LTM from chest CT images migth bring important information about both tissue destruction of the parenchyma at low densities and on the increase of high density tissue, both caused by emphysema. In addition, the monoexponential fitting of the lung volume curve versus LTM migth be an alternative to indices based on arbitrary thresholds and migth be used to reduce the effect of lung volume on the densitometry indices.